Forming zone of detection of radio wave sensors - Storozh, Volodymyr; Ilnits`kyi, Ivan; Bratkovs`kyi, Roman (Видавництво Львівської політехніки, 2012)
The results of the study design and method of forming the width of the zone of detection of radio wave sensors.
Keywords: Radio wave sensor; integrated antenna; zone of detection